Geophysical and Structural Survey in the Diagnosis of Leaks at a Fuel Station in a Uranium Mine in Decommissioning Phase (Poços de Caldas, Brazil) - Moreira, César Augusto [UNESP]; Helene, Lívia Portes Innocenti; Hartwig, Marcos Eduardo; Lourenço, Rebeca [UNESP]; do Nascimento, Matheus Mistrinel Pacine Feitoza [UNESP]; Targa, Debora Andrade [UNESP] (Springer Nature, 2021)
Mining enterprises are, in essence, landscape modifiers and sources of long-term environmental degradation. The development of activities within the mines requires a complex logistical system for better functioning. It is common to have gas stations in the vicinity of mining areas as a support for supplying vehicles and machines. Inadequate operation and the absence of monitoring, as well as a planned closure of the activities of these stations, may impose risks of contamination of the geological environment. This work presents the efficiency of using electrical resistivity tomography (ERT) to map aged hydrocarbon in the subsurface in a former gas station area in a uranium mine. The presence and flow of hydrocarbons in the geological environment are also investigated through structural analysis of the area integrated with the geophysical results. The ERT results show a clear connection between the low-resistivity anomalies contained in the subsoil and the presence of the rock mass. Of particular interest, the ERT results made it possible to model the fractures contained in the subsoil and that condition a certain flow orientation between porous and fractured systems. The integrated analysis of geophysical and structural surveys proved to be essential in cases of fractured aquifer contamination.
Keywords: diesel; ERT; fractured aquifer; gasoline; Mining